2016
DOI: 10.1111/jdv.13913
|View full text |Cite
|
Sign up to set email alerts
|

Survival of acral lentiginous melanoma in the National Cancer Institute of Colombia

Abstract: Prognosis of ALM in Colombia is relatively poor, particularly for patients with higher clinical stage. The large proportions of ALM diagnosed in stage III and IV explain the relatively poor survival, and illustrate the importance of improving prognosis by lowering stage at diagnosis through better education and early detection programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
26
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 15 publications
5
26
0
7
Order By: Relevance
“…Our findings concur with previous publications which have evaluated ALM patients in according to ethnicity (Caucasians and other ethnic groups, such as blacks, Hispanics, and Asians) in the same studies [1, 2, 4, 5, 8] and in separate studies [3, 6, 7]. In 17 population-based cancer registries, with a total number of 1,413 American subjects with histologically confirmed cases of ALM, the proportion of ALM among all melanoma subtypes was greatest in nonwhites, accounting for 36% of all melanomas in blacks, 18% in Asian/Pacific Islanders, 9% in Hispanic whites, and only 1% in non-Hispanic whites [1].…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Our findings concur with previous publications which have evaluated ALM patients in according to ethnicity (Caucasians and other ethnic groups, such as blacks, Hispanics, and Asians) in the same studies [1, 2, 4, 5, 8] and in separate studies [3, 6, 7]. In 17 population-based cancer registries, with a total number of 1,413 American subjects with histologically confirmed cases of ALM, the proportion of ALM among all melanoma subtypes was greatest in nonwhites, accounting for 36% of all melanomas in blacks, 18% in Asian/Pacific Islanders, 9% in Hispanic whites, and only 1% in non-Hispanic whites [1].…”
Section: Discussionsupporting
confidence: 81%
“…Phan et al [3] found that the prognosis of ALM in Whites was poor; the 5-year survival rate was 76%. Similar unfavorable survival results emerged from other studies in Hispanic patients [4, 5]. The 5-year overall survival of 90 Colombian ALM patients was only 54% [4], and ALM was an independent risk factor for decreased survival in Mexican melanoma patients ( p = 0.004) [5].…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations